The resting-brain of obsessive–compulsive disorder. (30th August 2019) - Moreira, Pedro Silva; Marques, Paulo; Magalhães, Ricardo; Esteves, Madalena; Sousa, Nuno; Soares, José Miguel; Morgado, Pedro
Highlights: We compared functional connectivity between 40 OCD and 40 healthy individuals. OCD patients had reduced connectivity within visual and sensorimotor networks. OCD patients had increased connectivity between default-mode and cerebellar networks. OCD patients had decreased connectivity between sensorial networks. Connectivity between these networks may modulate the manifestation of mood states. Abstract: Obsessive–compulsive disorder (OCD) is one of the most debilitating psychiatric conditions, having a dramatic impact on patients' daily living. In this work, we aimed to explore resting-state functional connectivity in OCD patients, using an independent component analysis. Eighty individuals (40 patients and 40 healthy controls) performed a resting state fMRI protocol. OCD patients displayed reduced functional connectivity (FC) in visual and sensorimotor networks. In addition, patients displayed decreased FC between sensory networks and increased FC between default-mode and cerebellar networks.